Characterisation of 19th and 20th century Chinese paper. Issue 1 (December 2017) - Brown, Natalie; Lichtblau, Dirk; Fearn, Tom; Strlič, Matija
Abstract The chemical and physical properties of 19th and 20th century Chinese papers were investigated using a variety of material characterisation methods. A reference collection of 178 Chinese papers, dating from 1799 to 1990 was used, and properties such as pH, degree of polymerisation (DP), lignin content, and tensile strength (zero-span) were determined. Most of the papers were of approximately neutral pH, had a low lignin content and DP similar to pre-19th century European rag paper. It was found that the high inhomogeneity and the typical paper thinness affected tensile testing and as a result, a modified method for zero-span tensile strength test was developed. Using near infrared spectroscopy (NIR), proof-of-concept partial least squares (PLS) applications were developed for determination of tensile strength, pH, DP and for dating of the samples. For the latter, using post-1900 papers, the error of cross validation was 13 years. The presence of lignin was modelled using linear discriminant analysis (LDA), where the model could distinguish between high and low lignin content with 88% accuracy. Using one or multiple sheets for transmission NIR spectroscopy led to PLS results of similar quality, which was attributed to material inhomogeneity.